2008
DOI: 10.1002/humu.20706
|View full text |Cite
|
Sign up to set email alerts
|

MID1 mutations in patients with X-linked Opitz G/BBB syndrome

Abstract: Communicated by Arnold MunnichMutations in the MID1 gene are responsible for the X-linked form of Opitz G/BBB syndrome (OS), a disorder that affects the development of midline structures. OS is characterized by hypertelorism, hypospadias, laryngotracheo-esophageal (LTE) abnormalities, and additional midline defects. Cardiac, anal, and neurological defects are also present. The expressivity of OS is highly variable, even within the same family. We reviewed all the MID1 mutations reported so far, in both familia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
63
1
8

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(75 citation statements)
references
References 44 publications
(95 reference statements)
3
63
1
8
Order By: Relevance
“…Various mutations of MID1 have been identified in human patients with X-linked OS (25), and it has been reported as an E3 ligase for PP2Ac (13). However, the role of Mid1 in mammalian neural development and function is largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Various mutations of MID1 have been identified in human patients with X-linked OS (25), and it has been reported as an E3 ligase for PP2Ac (13). However, the role of Mid1 in mammalian neural development and function is largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…As hypospadias forms part of OS, 8 we hypothesized that the gene responsible for the X-linked form of OS, the MID1 gene, might be involved in the development of hypospadias as a mild form of OS. 9,10 We identified one nonsense mutation, one missense mutation and two synonymous variants. We also found there was significant difference between the rare allele frequency of SNP c.1230G4A in cases as compared with controls.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in the MID1 gene cause the X-linked form of Opitz G/BBB syndrome (OS, characterized by midline abnormalities such as hypertelorism, cleft lip/palate, tracheo-esophageal abnormalities, cardiac defects and hypospadias). [8][9][10] The function of MID1 is highly conserved in vertebrates, and experiments conducted in mice and chicken showed that MID1 expression correlated well with the tissues affected in OS. 11,12 In situ hybridization studies on human embryos showed that the expression of MID1 was localized in undifferentiated cells of midline structures including the urogenital system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Com formas mais brandas acometendo as mulheres, as quais apresentam hipertelorismo sem malformações genitais, e sem evidência de transmissão homem-homem, aventou-se a hipótese de que a herança poderia ser ligada ao cromossomo X . Com a evolução dos estudos sindromológicos, o fenótipo referente à herança ligada ao X foi definitivamente estabelecido (ROBIN; OPITZ; MUENKE, 1996;MAY et al, 1997;QUADERI et al, 1997;DE FALCO et al, 2003;RUSSOLILLO;MERONI, 2008 MERONI, 2011).…”
Section: Revisão De Literaturaunclassified